Absence of disease related prion protein in neurodegenerative disorders presenting with Parkinson's syndrome. Issue 10 (October 1994) - Jendroska, K; Hoffmann, O; Schelosky, L; Lees, A J; Poewe, W; Daniel, S E
Abstract : Movement disorders presenting with parkinsonism may share histopathological features with Creutzfeldt-Jakob disease, a spongiform encephalopathy caused by the accumulation of pathological prion protein in brain. To investigate a possible aetiological link between these conditions and Creutzfeldt-Jakob disease, histoblot immunostaining for pathological prion protein was carried out in 90 cases including idiopathic Parkinson's disease, multiple system atrophy, diffuse Lewy body disease, Steele-Richardson-Olszewski syndrome, corticobasal degeneration, and Pick's disease. Pathological prion protein was identified in four controls with Creutzfeldt-Jakob disease but not in any of the other diseases examined. The findings suggest that an aetiological role for prions in these movement disorders is unlikely. Histoblotting provides a useful method for screening large areas of tissue for the presence of pathological prion protein and may be helpful in the differential diagnosis of difficult cases.